Elaboración de una propuesta de certificación de productos agroecológicos en la provincia de Cotopaxi. - Espinoza Cevallos, Jaqueline Estefanía (2020)
The present execution of this research project, has as its main objective a proposal for certification of agroecological products in Cotopaxi Province, in order to obtain clean and safe products, based on the productive reality, the main production areas will be determined, fairs, and level of acceptance of agroecological products in consumers. The direct beneficiaries in carrying out this research will be men and women who are dedicated to the cultivation of agroecological products, and thus obtain the level of acceptance of them in Cotopaxi Province. The mechanisms of action of the products should be studied based on the ecological principles that operate and direct the productive systems, additionally using ancestral techniques and methods that characterize the production of these products, with benefit for the consumption of the population, which will finally be accepted. in the market through a national regulation, naive code and agribusiness standards, establishing for a productive purpose in the market. Finally, in order to comply with the regulations, bibliographic review activities, field visits to verify soil, water and external media will be carried out, applying the use of tools such as surveys, interviews, producers and consumers, all of which will allow obtaining a certification from the institution competent to ensure that market products meet the quality characteristics of an agro-ecological product in the Province of Cotopaxi.